Degradación de NO₂ empleando un reactor fotocatalítico usando TiO₂ como catalizador (2016)
A photocatalytic reactor was elaborated and employed to reduce the N0₂ concentration in air. Ti0₂ was used as photocatalysts and an automatized system of data acquisition, based in LabVIEW Software, was fitted to the reactor to monitor degradations. The photo-reactor allowed to obtain decreases in N0₂ concentration up to 95 in 90 min.